تدويل المؤسسات الصغيرة والمتوسطة - دراسة حالة مؤسسة FRIGOMEDIT فرع الوادي - الساسي, عاد; الطاهر, صوالح عمار; عبد القادر, هاني (جامعة الوادي - University of Eloued, 2023)
تعتبر المؤسسات الصغيرة والمتوسطة في الدول المتقدمة المحرك الرئيسي لنشاطها الاقتصادي وأحد اهم الحلول الداعمة لنموها الاقتصادي وتحقيق التنمية، وهذا ما حذا بالجزائر الى انتهاج هذا المسار والاهتمام أكثر بالمؤسسات الصغيرة والمتوسطة بدعمها وتأهيلها وكذا المساهمة بتهيئة الظروف لتدويل أنشطتها للمساهمة في تنمية الصادرات وتنوعها. نهدف من خلال هاته الدراسة الى ابراز فاعلية تدويل المؤسسات الصغيرة والمتوسطة ودور الدعم الحكومي في تأهيل ودعم المؤسسات الصغيرة والمتوسطة نحو التدويل، وعرض تجربة مؤسسة محلية في التصدير كآلية من اليات التدويل. وبعد استخدام المنهج التحليلي، تم التوصل الى النتائج التالية: -ان هناك خلل كبير في مناخ الاستثمار للمؤسسات الصغيرة والمتوسطة نتيجة التقلبات في النهج التنموي المتبع-ان نجاح مؤسسة بالأسواق المحلية لا يعتبر كمعيار لنجاحها دوليا-تفضل اغلبية المؤسسات المحلية التصدير كألية سهلة والاكثر أمان والاخف ضررا مقارنة بالطرق الاخرى في التدويل. Small and medium-sized enterprises in developed countries are the main engines of their economic activities and one of the most important solutions to support their economic growth and development, which has led Algeria to take this path and place greater emphasis on institutions. Support and qualify small and medium-sized enterprises, create conditions for internationalization of their activities, and contribute to export development and diversification. Thus, we aim through this study, to highlight the effectiveness of the internationalization of small and medium enterprises and the role of government support in qualifying and supporting small and medium enterprises towards internationalization, and to present the experience of a local enterprise in exporting as one of the methods of internationalization. After using the analysis method, the following results are obtained: -Due to fluctuations in development methods, there is a significant imbalance in the investment environment of small and medium-sized enterprises- The success of an enterprise in the local market is not regarded as the standard of its international success- The majority of local institutions prefer exporting as an easy, safest and least harmful method compared to other methods of internationalization.
Keywords: المؤسسات الصغيرة والمتوسطة، تدويل، تصدير، الاستثمار; small and medium enterprises, internationalization, export, investment